The relationship between casino corporate social responsibility and casino customer loyalty. Issue 4 (June 2019) - Chen McCain, Shiang-Lih; Lolli, Jeffrey C; Liu, Emma; Jen, Eric
Corporate social responsibility (CSR) has become a popular, and even expected, strategy for promoting an organization's public persona. CSR is particularly important in the casino industry since many customers associate the casino industry with negative images such as crime and drugs; therefore, casinos try to enhance their social image through CSR activities. This study investigated how casinos' CSR activities (economic, legal, ethical, and philanthropic) influenced customer loyalty (CL). Partial Least Squares (PLS)-structural equation modeling analysis was used to examine the hypotheses on a sample of 251 casino's customer in the United States. Results of this study showed that the dimensions of philanthropic and legal responsibilities had varying effects on CL. In contrast, economic and ethical responsibilities didn't significantly affect CL.